Determinants of Stunting Handling Policies in Enggano Subdistrict, North Bengkulu Regency - Tanumiharja, Yemima Febrilianti; Yogopriyatno, Jatmiko; Zulhakim, Abdul Aziz (KnE Social Sciences, 2025)
Stunting remains a priority public health issue in North Bengkulu Regency, which has been designated as a stunting reduction intervention locus under the Decree of the Minister of PPN / Bappenas No. 10 / M.PPN / HK / 02/2021, with a prevalence of 22.8%. However, Enggano Sub-district, an outer island region, has remarkably reduced its stunting rate to just 0.29%, owing to a combination of interrelated success factors. This study aims to identify the key determinants behind the effective stunting management policies in Enggano Sub-district. A qualitative research approach was used, with data collected through observation, interviews, and documentation. Data analysis followed five stages: data organization, reading and recording, coding, describing and compiling, and interpreting and reporting findings. The results highlight that the success in addressing stunting in Enggano is driven by strong cross-sectoral cooperation, including the leadership of the sub-district head coordinating stakeholders, the active role of the puskesmas in policy implementation, and the commitment of village governments in executing programs. Additional contributing factors include regular monitoring of child growth, nutrition education for pregnant women, and the distribution of supplementary food to at-risk children. Community engagement and effective coordination among stakeholders further strengthen the success of stunting prevention efforts in the sub-district.